PENINGKATAN PENGETAHUAN MASYARAKAT DESA PULAU PELAPIS MELALUI TANAMAN OBAT KELUARGA (TOGA) UNTUK MENDUKUNG KESEHATAN DAN KESEJAHTERAAN KELUARGA - Linda, Riza; Raynaldo, Adityo; Saputra, Robin; Zibar, Zan; Marista, Etha; Shofiyah, Sofi Siti (Program Studi Ilmu Kelautan, FMIPA Universitas Tanjungp, 2024)
Health is a primary human need to be able to carry out life activities perfectly. Fulfillment of health can be achieved by fulfilling adequate and balanced nutrition. One of the nutrients that must be met is the need for carbohydrates, protein and vitamins. These elements can be obtained from animals and plants. Obtaining a nutritional source that is very cheap, easy to obtain and can provide greenery and aesthetic value around the yard of the house is by making Toga. Education to the community about family medicinal plants (Toga) in Pulau Peputar Village is very necessary considering that Pulau Peputar Village is one of the tourist villages. Pelalu Island Village, Karimata District, North Kayong Regency. The method used in this activity is in the form of counseling, including conveying theory and discussion. Participants will get theories about the importance of health, especially fulfilling balanced nutrition through making Toga and the importance of greenery and beauty in supporting village government programs, namely increasing human resources in ecotourism villages. The stages of this activity include preparation and extension activities. The counseling contains an introduction to the types of medicinal plant species and their uses. Demonstrations regarding the potential and use of medicinal plants in the community in Pulau Pelapis Village were carried out at the village office/school building. The aim of this community service activity program is to improve the health of family members through a program of using family medicinal plants as family herbal medicine. Socialization about Toga apart from supporting health, also provides environmental beauty, preserves plants and can provide family welfare. The results of this activity show an increase in participants' knowledge of potential plant species that have medicinal properties.Keyword: Health, Nutrition, TOGA, education, Pulau Pelapis village